Women’s Oppression Through Patriarchal Culture in Novel Suti by Sapardi Djoko Damono - Utomo, Udiarso Cahyo; Supriyanto, Teguh (Pascasarjana Universitas Negeri Semarang, 2018)
The patriarchal culture that developed in this novel led to acts of oppression against women who seemed to have no value for a man. The purpose of this study was to find out the style of language used, social strata, forms and motives for the oppression of women in the novel Suti by Sapardi Djoko Damono. The approach used in this study is to use a literary sociology approach and a feminist approach. The results of the study found, among others, the study of language style used is a term in Javanese to emphasize behavior and figure characters. Social strata are groups of nobles and ordinary groups, as well as attempts to maintain social classes. The forms of oppression included (1) the betrayal of marriage, (2) the abolition of women's rights through patriarchal culture, (3) the marginalization of women. The motive of suppression of women in Suti's novel is to get sexual satisfaction with other women who are not legitimate wives and the behavior wants to be considered as a fairness, thus it can be concluded that oppression of women through patriarchal culture is merely to get satisfaction without interference or resistance from the women's side by utilizing all its limitations where this kind of thing also wants to be considered as a natural thing.